Pengaruh stres kerja terhadap kinerja pada tenaga kesehatan dimasa pandemi Covid-19 - Djamaluddin , Nurul Maycfani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Job stress is the tension experienced by employees because of an imbalance between job demands and the ability of employees to complete their work. So this study aims to determine the effect of work stress on the performance of health workers during the COVID-19 pandemic. The hypothesis in this study is that, first, work stress does not affect the performance of health workers during the COVID-19 pandemic and, second, work stress affects the performance of health workers during the COVID-19 pandemic. The method in this study uses quantitative research methods. The subjects in this study were 44 health workers who work in hospitals that treat COVID-19 patients. The measuring instrument used is the Likert scale. The results of this study show that work stress on health workers during the COVID-19 pandemic has a positive and significant effect on the performance of health workers, meaning that the performance of health workers tends to increase, which results in stress at work during the COVID-19 pandemic, so that the relationship between work stress and performance, whether it is strong, moderate, or low, there will still be a significant effect.